2020
DOI: 10.37291/2717638x.20201128
|View full text |Cite
|
Sign up to set email alerts
|

STEM starts early: Views and beliefs of early childhood education stakeholders in Tanzania

Abstract: For about a decade, Tanzania has intensely focused on developing literacy and numeracy skills in pre-primary and early grades programs. Recently, the attention has shifted towards the significance of teaching Science, Mathematics, Technology and Science (STEM) in the early years. To enhance the 21st century skills necessary for building a middle income and knowledge-based economies, the existing empirical evidence emphasizes the need for STEM education starting from pre-primary level.  This paper aims to unpac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Finland recruits the top third of each graduate cohort as school teachers (Ismail & Awang, 2017). The current study's findings are consistent with Ndijuye, Mligo, and Machumu (2020), Ali et al (2022) in Tanzania and Kamwitha and Ibrahim (2020) in Kenya on adequately trained teachers in ECE. In emphasis, Ntumi (2016) in Ghana found that most preschool teachers do not understand the early childhood curriculum as challenging.…”
Section: It Is Six Years Since I Started Teaching Pre-primary Classes...supporting
confidence: 88%
“…Finland recruits the top third of each graduate cohort as school teachers (Ismail & Awang, 2017). The current study's findings are consistent with Ndijuye, Mligo, and Machumu (2020), Ali et al (2022) in Tanzania and Kamwitha and Ibrahim (2020) in Kenya on adequately trained teachers in ECE. In emphasis, Ntumi (2016) in Ghana found that most preschool teachers do not understand the early childhood curriculum as challenging.…”
Section: It Is Six Years Since I Started Teaching Pre-primary Classes...supporting
confidence: 88%
“…It should be noted that a number of studies suggest that in teaching reading skills to early grades, pupils' cultural and linguistic diversities should be considered to facilitate learning of Kiswahili reading skills (Agbevivi, 2022;Mohohlwane et al, 2023;Serede & Mwoma, 2022). On the absence of PPE among grade one pupils, these findings corroborate those of Mabagala and (2019); Ndijuye et al, (2020); Ndijuye and Beatus, (2022); Serede and Mwoma, (2022). Serede and Mwoma, (2022) develop this as a major impediment in teaching phonemic awareness and alphabet knowledge in grade one and stressed that PPE should be taken seriously as it has a significant impact on pupils' learning and development of reading skills in primary school.…”
Section: Discussionsupporting
confidence: 54%
“…Among naturalized citizens from refugee backgrounds, the language most frequently spoken at home reflects students' country of origin. For example, children from Burundi predominantly speak Kirundi (Ndijuye & Tandika, 2020, 2022b). While Kiswahili is widely spoken in Tanzania, children from these groups encounter it when starting formal education.…”
Section: Factors Affecting Early Learning Of Children Of Naturalized ...mentioning
confidence: 99%